Childcare and education quality assurance at private preschools: A case study in Hanoi, Vietnam - Thao Bich Thi Nguyen (Vietnam Journal of Education, 2020)
Research on quality assurance (QA) over nurturing, caring and educating preschool children is an urgent and crucial issue, especially at private preschools. Using questionnaire survey methods, the study evaluates the situation of ensuring the quality of nurturing and educating children in private preschools regarding the following main aspects: establishing quality standards of child nurturing and education; building a quality assurance system and procedure for preschools’ childcare and education; financial and infrastructure conditions for QA activities to nurture and educate children; the community’s participation into private preschools’ activities; developing a culture of preschools’ childcare and education quality. The research significance lies in the implications from the results to improve QA of nurturing and educating children in private preschools in Hanoi, Vietnam.